Elucidation of the binding mechanism of astragaloside IV derivative with human serum albumin and its cardiotoxicity in zebrafish embryos - Wu, You-Jiao; Li, Zhan-Hua; Li, Jiu-Yan; Zhou, Yan; Wang, Run-Yue; Chen, Xiao-Yi; Qing, Lin-Sen; Luo, Pei (Frontiers in Pharmacology, 2022)
LS-102 is a new derivative of Astragaloside IV (AGS IV) that has been shown to possess potentially significant cardioprotective effects. However, there are no reports concerning its interaction with human serum albumin (HSA) and toxicology in vertebrates. The present investigation was undertaken to characterize the interaction of AGS IV and LS-102 with HSA by means of equilibrium dialysis and UHPLC–MS/MS methods, along with computational methods. Noteworthy, effects of AGS IV and LS-102 have been studied in vivo using the zebrafish embryo model. Markers related to embryonic cardiotoxicity and thrombosis were evaluated. We showed that plasma protein binding rate of AGS IV (94.04~97.42%) was significantly higher than that of LS-102 (66.90~69.35%). Through site marker competitive experiments and molecular docking, we found that AGS IV and LS-102 are located at the interface of subdomains IIA and IIIA, but site I may be the primary binding site. Molecular dynamics revealed that AGS IV showed a higher binding free energy mainly due to the stronger hydrophobic and hydrogen bonding interactions. Moreover, the secondary structure implies no obvious effect on the protein structure and conformation during the binding of LS-102. LS-102 significantly ameliorated the astramizole-induced slowing of heart rate and increased SV-BA spacing; and prevented arachidonic acid-induced thrombosis in zebrafish. This work for the first time revealed that LS-102 binds to HSA with reversible and moderate affinity, indicating its easy diffusion from the circulatory system to target tissue, thereby providing significant insights for understanding its pharmacokinetic and pharmacodynamic properties when spread in the human body. Apart from that, it provides a reference for the rational clinical application of LS-102 in the cardiovascular field.